Structural Intervention In Increasing The Achievement Of Covid-19 Vaccination In Elderly Group In Bandara Kulon Village, Bagor District Nganjuk - Susi Jumiani; Ardi Bastian (Journal of Hospital Management and Services, 2022)
The Covid-19 virus attacks many vulnerable groups, one of which is the elderly group. The achievement of Covid-19 vaccination in the elderly group is still low. Of the 333 elderly people who have been successfully vaccinated, only 125 have been vaccinated. The purpose of this study was to determine the effect of structural interventions given to the elderly group on increasing Covid-19 vaccination achievements.The method used is a quantitative method with Pre-experimental designs one-group pretest-posttest design. The data used is data from the Bagor Health Center as of December 30, 2021. The sampling technique uses Simple Random Sampling.The total sample of this study was 137 respondents. Based on the results of the mc nemar test, a significance value was obtained, namely, the value of 2obs = 125.008 and p-value of 0.000 with = 0.05. So there is a difference in willingness to be vaccinated between before the intervention and after the intervention. Structural interventions carried out in the elderly group who have not received the covid-19 vaccination can increase the achievement of the covid-19 vaccination in the elderly group so that it can accelerate the formation of herd immunity in the community.